Preventive and Curative Effects of Calendula-Oficinalis Leaves extract on Acetaminophen-Induced Hepatotoxicity - Ali, Jamshed; Khan, A. Hameed (Journal of Postgraduate Medical Institute, 2011)
To assess the hepatoprotective potential of leave of Calendula officinalis against experimentally produced liver damaged in animals using acetaminophen as model hepatotoxin. This study was conducted at Department of Pharmacy University of Peshawar preliminary experiements were performed in mice to estimate the protective effect of plant material against lethal dose of acetaminophen (1gm/kg). Acute toxicity of plant material up to a dose of 3gm was assessed in mice to note any behavioural changes and mortality. Hepatic damagein rats was induced by oral acetaminophen (640 mg/kg). The effect of methanolic extract of leav es of Calendula officinalis was investigated against acetaminophen induced hepatic damage in 30 male, albino rats. these results indicate that the crude extract of calendula officinalis leave exhibits hepatoprotective action.